2002
DOI: 10.1063/1.1446115
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and loss separation in iron powder soft magnetic composite materials

Abstract: New developments in powder metallurgical composites make soft magnetic composite ͑SMC͒ material interesting for application in electrical machines, when combined with new machine design rules and new production techniques. In order to establish these design rules, one must pay attention to electromagnetic loss characteristics of SMC material. In this work, five different series of iron based SMCs are produced and studied: ͑1͒ Pure iron powder with resin; ͑2͒ sintered iron based powders; ͑3͒ pure iron powder wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Therefore, the rod samples were characterised directly on a small size single sheet tester (SST), which was calibrated to the standard Epstein frame [9]. The dimensions and detailed description of the SST used by us are given in a previous paper [10]. The calibration of the SST was done on a non-oriented electrical steel sheet.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the rod samples were characterised directly on a small size single sheet tester (SST), which was calibrated to the standard Epstein frame [9]. The dimensions and detailed description of the SST used by us are given in a previous paper [10]. The calibration of the SST was done on a non-oriented electrical steel sheet.…”
Section: Methodsmentioning
confidence: 99%
“…A disadvantage of the composite materials is the lower permeability in contrast to laminated sheets which implies that they cannot be used as a direct replacement without abatement in performance [2].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that q R decreases with the increasing magnetic particle size: for compared to similar composites investigated e.g. in [29][30][31], revealing good insulation of particles.…”
Section: Thermal and Electrical Propertiesmentioning
confidence: 88%